Aplikasi Mobile SiPJuHOG (Sistem Presensi Jurnal Harian Online Guru) - Ladayya, Ulfa; Sari, Dian Permata; Widodo, Suprih; Abdulmajid, Nuur Wachid; Perdana, Zia Imam (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2025)
A teacher has many responsibilities, from teaching activities to fulfilling all existing administration. The existence a social gap between ASN and non-ASN regarding attendance is one of the problems at the School. Another problem is that attendance is written directly on the class agenda, making difficult for the School to monitor teacher attendance and there's no daily teacher journal attendance system at SMKN 2 Purwakarta. Based on this, SiPJuHOG (Teacher Online Daily Journal Presence System) mobile application was built to solve the problem. The purpose of research: 1) Make easier and faster for teachers to fill in their daily journal attendance; and 2) Make easier for schools to recap the attendance of ASN and non-ASN teachers when teaching. The type and design of research used is prototype method. Based on research, conclusions were obtained: 1) SiPJuHOG Mobile Application was built using dart language, flutter framework, PHP, SQL, and using wampserver.  Based on manual testing using ‘Browserstack’ all functions run well; and 2) The results of mobile application functionality test to users succeeded through all function instruments. The usability test results obtained total score of 71,59 with the category ‘GOOD’ (adjective ratings), grade C (grade scale), and ‘ACCEPTABLE’ (acceptability ranges). Meanwhile, efficiency test using ‘DevTools’ obtained an average frames per second of 58. This means that the application runs quite well in terms of visual performance. Finally, portability test conducted during mobile user testing and using ‘BrowserStack’ obtained results according to criteria (running on Samsung, Oppo, Vivo, and Motorola mobile phones).